Delegation of regulation - Tapas Kundu; Tore Nilssen (University of Oslo, Department of Economics, 2017)
We develop a model to discuss a government's incentives to delegate to bureaucrats the regulation of an industry. The industry consists of a polluting firm with private information about its production technology. Implementing a transfer-based regulation policy requires the government to make use of a bureaucracy; this has a bureaucratic cost, as the bureaucracy diverts a fraction of the transfer. The government faces a trade-off in its delegation decision: bureaucrats have knowledge of the firms in the industry that the government does not have, but at the same time, they have other preferences than the government, so-called bureaucratic drift. We study how the bureaucratic drift and the bureaucratic cost interact to a affect the incentives to delegate. Furthermore, we discuss how partial delegation, i.e., delegation followed by laws and regulations that restrict bureaucratic discretion, increases the scope of delegation. We characterize the optimal delegation rule and show that, in equilibrium, three different regimes can arise that differ in the extent of bureaucratic discretion. Our analysis has implications for when and how a government should delegate its regulation of industry. We find that bureaucratic discretion reduces with bureaucratic drift but that, because of the nature of the regulation problem, the effect of increased uncertainty about the firm's technology on the bureaucratic discretion depends on how that uncertainty is reduced.
Keywords: D02; H10; L51; 330; Bureaucracy; Delegation; Regulation